DAVLAT XARIDLARI NAZORATI: MONITORINGNI OʻZBEK MODELINING INSTITUTSIONAL TAHLILI - Юлдашева, Надира (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article presents an institutional analysis of the monitoring and control system in the field of public procurement in the Republic of Uzbekistan. The study is based on the study of the evolution of regulatory mechanisms, digital platforms and organizational and managerial decisions aimed at ensuring transparency, legality and efficiency of using budget funds. Particular attention is paid to the substantive distinction between the concepts of “control” and “monitoring”, the introduction of a risk-oriented approach, the development of compliance control and the transformation of the digital procurement environment. Based on empirical data for 2022–2024, the effectiveness of institutional reforms is substantiated and key trends in improving the national model of public financial management are identified.